Pengaruh Indikator Makroekonomi dan Karakteristik Perusahaan Terhadap Harga Saham Syariah Sektor Industri Barang Konsumsi - Kristianingsih Kristianingsih; Fifi Afiyanti Tripuspitorini; Sekar Putri Yuandra (Jurnal Maps (Manajemen Perbankan Syariah), 2022)
This study aims to determine the effect of macroeconomic factors which include inflation, interest rates, rupiah exchange rates, and company characteristics consisting of ROE, CR and company size on sharia share prices in the consumer goods industry sector on the Indonesian Sharia Stock Index (ISSI) for the period 2014-2014. 2020. The research method used is descriptive quantitative method using multiple linear regression analysis techniques. This study uses secondary data from the official website of the Indonesia Stock Exchange (IDX), the Central Statistics Agency (BPS), the Financial Services Authority (OJK), Bank Indonesia (BI). The number of samples used as many as 25 companies that meet the research criteria by using purposive sampling technique. Hypothesis testing is done by using a path diagram. The results of this study indicate that macroeconomic factors consisting of inflation, interest rates, and the rupiah exchange rate partially have no effect on stock prices. Company characteristic factors consisting of firm size, and CR have a positive influence on stock prices, while ROE has a negative effect on Islamic stock prices.